Relational database design clearly explained - Harrington, Jan L. (New York : Morgan Kaufmann Publishers, 2002)
Fully revised and updated, Relational Database Design, Second Edition is the most lucid and effective introduction to relational database design available. Here, you'll find the conceptual and practical information you need to develop a design that ensures data accuracy and user satisfaction while optimizing performance, regardless of your experience level or choice of DBMS. Supporting the book's step-by-step instruction are three case studies illustrating the planning, analysis, and design steps involved in arriving at a sound design. These real-world examples include object-relational design.
Entities and data relationships -- Historical antecedents -- The relational data model -- Normalization -- Database structure and performance tuning -- Codd's rules -- Integrating objects -- Using SQL to implement a relational design -- Using CASE tools for database design -- Database design case study #1 : Mighty-Mite Motors -- Database design case study #2 : East Coast Aquarium -- Database design case study #3 : Independent Intelligence Agency.
Includes index.
Keywords: Relational databases; Relational databases -- Case studies; Database design; Electronic books; Case studies